Pengaruh Literasi Bisnis dan Toleransi Risiko Terhadap Keterampilan Kewirausahaan Karyawan - Didit Darmawan; Reny Nurani; Arif Rachman Putra; Rahayu Mardikaningsih; Siti Nur Halizah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine the effect of business literacy and risk tolerance on employee entrepreneurial skills in a business environment. This research method uses a quantitative approach by collecting data by distributing questionnaires to 100 employees from one of the industrial sectors in the city of Surabaya. Accidental sampling was used as a sampling technique in this study. Data were analyzed using multiple linear regression techniques to examine the effect of business literacy and risk tolerance on employee entrepreneurial skills. The results of this study reveal that business literacy and risk tolerance have a significant influence on employee entrepreneurial skills. Thus, this research contributes to deepening understanding of how business literacy and risk tolerance can affect the level of entrepreneurial skills of employees in a business environment. These findings can serve as a guide for companies in designing more effective training programs to enhance their employees' entrepreneurial skills